Professional self-efficiency of future teachers in the field of art education (Pedagogy of Higher and Secondary Education, 2009)
The meaning of forming the pedagogical self-efficacy in the context of European integration, analyzing the influence of the professional self-efficacy' of the teacher on his self-regulatory and all kinds of work varieties when studying the students with the purpose of forming the pedagogical self-efficacy of the future teacher of music of the European rate are investigated in this article.
Keywords: self-efficacy; pedagogical self-efficacy; reflexing; reflexing-evaluating environment; emotional stability